DNA Methylation Changes More Slowly Than Physiological States in Response to Weight Loss in Genetically Diverse Mouse Strains - Edillor, Chantle R.; Parks, Brian W.; Mehrabian, Margarete; Lusis, Aldons J.; Pellegrini, Matteo (Frontiers in Endocrinology, 2019)
Responses to a high fat, high sucrose (HFHS) diet vary greatly among inbred strains of mice. We sought to examine the epigenetic (DNA methylation) changes underlying these differences as well as variation in weight loss when switched to a low-fat chow diet. We surveyed DNA methylation from livers of 45 inbred mouse strains fed a HFHS diet for 8 weeks using reduced-representation bisulfite sequencing (RRBS). We observed a total of 1,045,665 CpGs of which 83 candidate sites were significantly associated with HFHS diet. Many of these CpGs correlated strongly with gene expression or clinical traits such as body fat percentage and plasma glucose. Five inbred strains were then studied in the context of weight loss to test for evidence of epigenetic “memory”. The mice were first fed a HFHS diet for 6 weeks followed by a low-fat chow diet for 4 weeks. Four of the five strains returned to initial levels of body fat while one strain, A/J, retained almost 50% of the fat gained. A total of 36 of the HFHS diet responsive CpGs exhibited evidence of persistent epigenetic modifications following weight normalization, including CpGs near the genes Scd1 and Cdk1. Our study identifies DNA methylation changes in response to a HFHS diet challenge that revert more slowly than overall body fat percentage in weight loss and provides evidence for epigenetic mediated “memory”.